Physical Factors in the Medical Rehabilitation of Children with Spinal Osteochondropathies - Evgeny M. Talkovsky; Dmitry Y. Vybornov; Nikolay I. Tarasov; Vladimir V. Koroteev; Vladislav F. Prikuls (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Aim. To conduct a targeted search for scientific literature sources aimed at compiling a review of data on the use of physical factors inthe medical rehabilitation of children suffering from spinal osteochondropathies.One of the most urgent and socially significant problems of modern medicine is the wide prevalence of orthopedic pathology, amongwhich the leading positions are occupied by diseases of the spine. In the population of children and adolescents, there has been arecent steady increase in pain syndromes of a vertebrogenic nature, leading to a violation of physical functioning. According to variouspopulation studies, the prevalence of this nosological form among the child population ranges from 0.42 to 37%. The prevalenceof Sheyerman-Mau disease in the general population of children and adolescents ranges from 0.4-8.3%. This pathology is the mostcommon among all osteochondropathies of childhood. To date, the etiology of spinal osteochondropathy is still unclear. Due to theasymptomatic course, the disease is not always diagnosed at the early stages of development which creates certain difficulties indiagnosing and prescribing effective treatment of the disease. Medical rehabilitation of children with spinal osteochondropathies isaimed at preventing further progression of deformity, improving posture, respiratory function and cardiovascular system and includes:rational motor mode and nutrition, general strengthening and hardening procedures, conservative orthopedic measures (wearing acorset, staying in a plaster bed), active correction of deformity (kinesotherapy), hydrokinesotherapy, massage, passive correction ofdeformity (treatment with position), physiotherapy (electrical muscle stimulation), sports (skiing, swimming). A special place in thereview is given to the presentation of the stages of medical rehabilitation of children with dorsalgia and adolescents who have undergonesurgical treatment for spinal osteochondropathies. Conclusion. When prescribing a personalized program of medical rehabilitation for children suffering from spinal osteochondropathies,the maximum positive dynamics of the course of the disease is achieved, which leads to an improvement in the quality of lifeand a decrease in disability among the children's population. The developed programs of medical rehabilitation of children will reducethe socio-economic losses from vertebrogenic pathology and will contribute to strengthening the health of the younger generationsof Russia.